2009
DOI: 10.3171/2009.2.jns08535
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of intraoperative high-resolution 2D ultrasound as an alternative to high–field strength MR imaging for tumor resection control: a prospective comparative study

Abstract: Intraoperative MR imaging is more precise in detecting small tumor remnants than 2D ultrasound. Nevertheless, the latter may be used as a less expensive and less time-consuming alternative that provides almost real-time feedback information. Its accuracy is highest in case of more confined, deeply located remnants. In cases of more superficially located remnants, its role is more limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 39 publications
1
56
0
1
Order By: Relevance
“…Another technique extensively used during neurosurgical procedures is intra-operative Ultrasounds (iUS); in recent years, multiple studies demonstrated their value in tumor detection during surgery, giving to iUS a foreground position in the field of intraoperative imaging [6][7][8][9]. The main point of value of iUS consists in obtaining a real-time scan repeatable as many times as necessary without the cost and the duration of other intraoperative techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Another technique extensively used during neurosurgical procedures is intra-operative Ultrasounds (iUS); in recent years, multiple studies demonstrated their value in tumor detection during surgery, giving to iUS a foreground position in the field of intraoperative imaging [6][7][8][9]. The main point of value of iUS consists in obtaining a real-time scan repeatable as many times as necessary without the cost and the duration of other intraoperative techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The objective 1 of surgical treatment is to achieve complete tumor resection with minimal damage to adjacent structures. The use of intraoperative image guidance, such as neuronavigation, magnetic resonance imaging (MRI) or ultrasonography (US), allows a more accurate detection of BM and reveals their anatomical relationships, possibly leading to better surgical results [16][17][18][19] . The present study reports a series of twenty patients with BM in whom intraoperative ultrasound, henceforth referred to as IOUS, was used to locate and guide tumor resection, as well as to prevent vascular injuries.…”
mentioning
confidence: 99%
“…However, iMRI requires very high standard infrastructure, which is expensive both in installment and maintenance, and its image acquisition time is relatively long. A popular alternative is ultrasound, which is also capable of real-time imaging of brain tumors [19,20]. However, its reliability in detecting tumor is less than that of iMRI; Gerganov et al compared the ultrasound technique with iMRI and pointed out that ultrasound could be used to detect more confined deeply located remnants of low-or high-grade tumors with high accuracy, though its accuracy is limited when detecting superficial remnants [20].…”
Section: Aimmentioning
confidence: 99%
“…It is capable of detecting neoplastic tumors because of their hyperechoic characteristic, which is associated with the structural abnormalities of brain tumors [19,20]. While it is very accurate in detecting confined, deeply located remnants of low-or high-grade tumors, the accuracy of ultrasound imaging is limited when detecting superficial remnants [20]. In addition, ultrasound is less likely to differentiate tumor from peritumoral edema that is also hyperechoic [21,22].…”
Section: Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation